Students’ reflections in teaching practicum: A case study of EFL pre-service teachers - Dwi Riyanti (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2020)
The importance of reflection in enhancing teachers’ professional development has been widely acknowledged. Yet, little is known about how EFL pre-service teachers do reflection and how they perceive reflective practice as one of the tools to improve their professional development. The current study attempts to address this gap by investigating how EFL pre-service teachers reflect on their teaching performances and perceive their reflective practices. Employing a qualitative case study, the study involved six teacher candidates who were taking microteaching. The data were gathered from an open-ended questionnaire made by the author, journal writing, participants' analysis on the videos of their teaching performances, and an interview with each participant. To triangulate the data, classroom observations and document analysis were also conducted. The obtained data were analyzed thematically based on emerging themes. The findings show that the participants did reflections in different stages of their teaching performances, reflecting on the surface level. In terms of how they view a reflection, the research participants perceive a reflection as a good practice because it gives them opportunities to look back and scrutinize what they did during their teaching practicum.